2017
DOI: 10.1002/jcb.25965
|View full text |Cite
|
Sign up to set email alerts
|

Novel Epigenetic Controlling of Hypoxia Pathway Related to Overexpression and Promoter Hypomethylation of TET1 and TET2 in RPE Cells

Abstract: CpG methylation of DNA takes part in a specific epigenetic memory that plays crucial roles in the differentiation and abnormality of the cells. The methylation pattern aberration of genomes is affected in three ways, namely DNA methyltransferase (DNMT), ten-eleven translocation (TET), and methyl-binding domain (MBD) proteins. Of these, TET enzymes have recently been demonstrated to be master modifier enzymes in the DNA methylation process. Additionally, recent studies emphasize that not only epigenetic phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Intriguingly, several studies have suggested that the transcriptional expression of the TETs themselves may further be regulated by hypoxia-induced changes in 5hmC (and thus potentially 5mC). Thus, the methylation status of both the Tet1 and Tet2 gene promoters in retinal pigment epithelial cells were found to become hypomethylated under conditions of chemically-induced hypoxia [90]. In addition, as stated above, we observed a transitory burst of 5hmC generation during early-differentiating ESCs that was dependent upon TET1 and was inhibited under low (1%) O 2 [44].…”
Section: Evidence For Regulation Of Tets By [O 2 ]supporting
confidence: 74%
See 1 more Smart Citation
“…Intriguingly, several studies have suggested that the transcriptional expression of the TETs themselves may further be regulated by hypoxia-induced changes in 5hmC (and thus potentially 5mC). Thus, the methylation status of both the Tet1 and Tet2 gene promoters in retinal pigment epithelial cells were found to become hypomethylated under conditions of chemically-induced hypoxia [90]. In addition, as stated above, we observed a transitory burst of 5hmC generation during early-differentiating ESCs that was dependent upon TET1 and was inhibited under low (1%) O 2 [44].…”
Section: Evidence For Regulation Of Tets By [O 2 ]supporting
confidence: 74%
“…In addition to the ability of [O 2 ] to regulate TET activity, multiple studies have demonstrated the transcriptional expression of TET enzymes to be dependent upon the cellular O 2 availability. Thus, increases in TET1/2 and 3 have all been reported in various cell types under hypoxic conditions [71,[90][91][92][93][94] which, in some cases, have been demonstrated to be dependent upon HIF1 [71,91,93]. As in the case of TET activity, the levels of expression of the different TET proteins show distinct patterns of sensitivity to different levels of hypoxia [93].…”
Section: Evidence For Regulation Of Tets By [O 2 ]mentioning
confidence: 93%
“…Furthermore, MMP8 facilitates SIRT1‐Zeb1 interaction through association with Zeb1 (Sun et al, ). Also, according to studies, a transcriptional repressor complex including SIRT1, Twist1, and methyl‐CpG binding domain (MBD) protein‐1, can suppress the expression of E‐cadherin (Alivand, Soheili, Pornour, Solali, & Sabouni, ; Xu, Zhu, et al, ) (Figure ).…”
Section: Sirt1 and Emt Promotionmentioning
confidence: 99%
“…DNA methylation and miRNA are important epigenetic markers that affect gene expression in cancerous cells (Loginov et al, ). Epigenetic phenomena controls both mRNA and miRNA expression of cancers; therefore, epigenetic events and miRNA could play mutual roles in BC (Alivand, Soheili, Pornour, & Sabouni, ; Loginov et al, ). The expression of miRNA plays a crucial role in the progression and metastasis of BC and can be distinguished in ductal to lobular morphologies, tumor subclones, and the stages and grades of BC (Loginov et al, ; Raychaudhuri et al, ).…”
Section: Introductionmentioning
confidence: 99%